Wound-healing capabilities of whale sharks (Rhincodon typus) and implications for conservation management. Issue 1 (4th February 2021) - Womersley, Freya; Hancock, James; Perry, Cameron T; Rowat, David
Abstract : Marine species, such as the whale shark, are being subjected to unprecedented levels of human influence in their natural habitats. They may be vulnerable to obtaining injuries while spending time in surface waters. This study explores injury characteristics and timeframes of injury recovery with a view to inform management. Abstract: Wound healing is important for marine taxa such as elasmobranchs, which can incur a range of natural and anthropogenic wounds throughout their life history. There is evidence that this group shows a high capacity for external wound healing. However, anthropogenic wounds may become more frequent due to increasing commercial and recreational marine activities. Whale sharks are particularly at risk of attaining injuries given their use of surface waters and wildlife tourism interest. There is limited understanding as to how whale sharks recover from injuries, and often insights are confined to singular opportunistic observations. The present study makes use of a unique and valuable photographic data source from two whale shark aggregation sites in the Indian Ocean. Successional injury-healing progression cases were reviewed to investigate the characteristics of injuries and quantify a coarse healing timeframe. Wounds were measured over time using an image standardization method. This work shows that by Day 25 major injury surface area decreased by an average of 56% and the most rapid healing case showed a surface area reduction of 50% in 4 days. All wounds reached a point of 90% surface area closure by Day 35. There were differences in healing rate based on wound type, with lacerations and abrasions taking 50 and 22 days to reach 90% healing, respectively. This study provides baseline information for wound healing in whale sharks and the methods proposed could act as a foundation for future research. Use of a detailed classification system, as presented here, may also assist in ocean scale injury comparisons between research groups and aid reliable descriptive data. Such findings can contribute to discussions regarding appropriate management in aggregation areas with an aim to reduce the likelihood of injuries, such as those resulting from vessel collisions, in these regions or during movements between coastal waters.